Porous bioceramics produced by inkjet 3D printing: Effect of printing ink formulation on the ceramic macro and micro porous architectures control. (15th December 2018) - Zhang, Boqing; Pei, Xuan; Song, Ping; Sun, Huan; Li, Huiyong; Fan, Yujiang; Jiang, Qing; Zhou, Changchun; Zhang, Xingdong
Abstract: Hierarchical structures with tailored macro/micro-porosity architecture play an important role in bone tissue regeneration. In 3D printing process, the printing ink formulation will influence on the ceramic macro and micro porous architectures. In this paper, HA powders of nano-sized grains (NP) with diameters of 30–50 nm, air jet milling powders (AP) with diameters of 10–30 μm, and spherical powder (SP) with diameters of 10–50 μm, were used as the initial printing materials in the printing ink formulations. The viscosity and the rheological behavior of printing inks were studied. The microstructure and morphology of the printed scaffold were observed and the mechanical properties of different types of scaffolds were tested. The results showed that the initial printing materials would influence on printing performance, both of the AP and SP inks may print porous scaffolds successfully. However, NP printing inks exhibited dramatic shrinkage and it is not suitable for 3D printing of bioceramics. The printing ink formulation also have effects on the ceramic macro and micro porous architectures and mechanical properties. The maximum compressive strength of SPS were 5.5 MPa, 3.2 MPa and 0.9 MPa with porosities of 60%, 70% and 80%, respectively. As the macroporosity decreases, the mechanical properties of the material would drop dramatically. With the same porosities, the compressive strength of APS were slightly higher than that of the SPS specimens.